2016
DOI: 10.3390/microorganisms4030034
|View full text |Cite
|
Sign up to set email alerts
|

Adhesion Properties of Lactic Acid Bacteria on Intestinal Mucin

Abstract: Lactic acid bacteria (LAB) are Gram-positive bacteria that are natural inhabitants of the gastrointestinal (GI) tracts of mammals, including humans. Since Mechnikov first proposed that yogurt could prevent intestinal putrefaction and aging, the beneficial effects of LAB have been widely demonstrated. The region between the duodenum and the terminal of the ileum is the primary region colonized by LAB, particularly the Lactobacillus species, and this region is covered by a mucus layer composed mainly of mucin-ty… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
95
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
3
3
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 137 publications
(100 citation statements)
references
References 104 publications
3
95
0
2
Order By: Relevance
“…Recent studies have indicated that the attachment of bacteria including the hydrophobicity and self-agglutination of the bacterial surface, lipoteichoicacid (LTA), exopolysaccharides (EPS) and related cell surface proteins to mucosal surfaces is the initial event in intestinal adhesion and colonization [38, 16]. Meanwhile, there are many surface proteins that mediate adhesion in lactobacillus have been reported, such as CmbA/Lar_0958, EF-Tu, GAPDH, GroEL, Lam29, MapA, MBF, Msa, Mub (Mub family), Pili, 32-Mmubp, FbpA and GroEL, etc [39-41]. Probiotics adhere to host intestinal mucus, intestinal epithelial cells, extracellular stroma by means of its surface proteins, and/or other bacteria lipodesmoic acid to effectively prevent pathogenic infection [42-44].…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have indicated that the attachment of bacteria including the hydrophobicity and self-agglutination of the bacterial surface, lipoteichoicacid (LTA), exopolysaccharides (EPS) and related cell surface proteins to mucosal surfaces is the initial event in intestinal adhesion and colonization [38, 16]. Meanwhile, there are many surface proteins that mediate adhesion in lactobacillus have been reported, such as CmbA/Lar_0958, EF-Tu, GAPDH, GroEL, Lam29, MapA, MBF, Msa, Mub (Mub family), Pili, 32-Mmubp, FbpA and GroEL, etc [39-41]. Probiotics adhere to host intestinal mucus, intestinal epithelial cells, extracellular stroma by means of its surface proteins, and/or other bacteria lipodesmoic acid to effectively prevent pathogenic infection [42-44].…”
Section: Discussionmentioning
confidence: 99%
“…Another commonly used clinical probiotic is Lactobacillus rhamnosus GG (ATCC 53103), which has been reported to have strong mucoadhesion primarily through SpaCBA pilus-mediated interactions 74 . Notably, both EcN and L. rhamnosus GG show moderate mucus-binding ability and use moonlighting proteins with the secondary function of mucus adhesion but have quite different binding characteristics.…”
Section: Escherichia Coli Nissle 1917 (Ecn) Is An Extensively Studiedmentioning
confidence: 99%
“…Efficacy of lactobacilli as probiotics derives from their ability to tolerate very low pH values, which allows them to survive transit through the stomach, and adhere to the mucus layer by surface structures such as pili and cell-wall anchored proteins [30]. Some of their beneficial activities are favouring GIT health by inhibiting the growth of pathogenic organisms with the production of lactic acid and other metabolites.…”
Section: Introductionmentioning
confidence: 99%